(untitled) (Studia theodisca, 2017)
This paper presents Hölderlin’s letter to Seckendorf of 12th March 1804 and links it both to his biography and to his poetry. The poet considers the idea of the picturesque and confirms a concept of art and poetry which prefers order, geometry and balance between earth and sky instead of variety, irregularity and roughness, characteristics of the picturesque; he considers the world as a system and a heavenly construction («Architektonik des Himmels»). The poet underlines then that his focus is now on the national element, in his difference from the Greeks, on «the study of the fatherland» and particularly on the destiny of «heroes, knights and princes» («Heroen, Ritter und Fürsten»). This short but complex letter results as a poetry program that Hölderlin will only partially realize in his late fragments.